Upaya Meningkatkan Pendapatan Masyarakat dengan Inovasi Olahan Singkong Ballndung - Hidayatul Umah, Restu Yulia (Proceedings of Annual Conference on Community Engagement, 2018)
Community Service Lecture (KPM) is part of the Tri Dharma of Higher Education. KPM IAIN Ponorogo in 2018 was held in 3 Sub-districts in Ponorogo, that is Badegan District, Sampung District, and Jambon District. The focus of devotion to this paper is on group 31 in Kresek Hamlet, Biting Village, Badegan District. The majority of Biting villagers become Target Households (RTS) poverty reduction programs. The approach in this service uses the Asset Based community Development (ABCD) approach, which is an approach to community empowerment by focusing on assets owned by the community. Assets developed to increase family income in Kresek hamlet, Biting Village, Badegan District are cassava with processing innovations named Ballndung.